Comparative growth dynamics in a discrete-time Marxian circuit of capital model - Deepankar Basu (University of Massachusetts, Department of Economics, 2011)
This paper develops a discrete-time formalization of the circuit of capital model presented by Marx in Volume II of Capital Marx (1993) as a tool for aggregate economic analysis of capitalist economies. The discrete-time formalization closely follows and extends the continuous-time formalization in Foley (1982, 1986a). The discrete-time model is used to address two important issues of interest to the heterodox economic tradition: profit-led versus wage-led growth, and the growth-reducing impact of non- production credit. First, it is demonstrated that both profit-led and wage-led growth regimes can be accommodated within the Marxian circuit of capital model. Second, it is demonstrated that the steady-state growth rate of a capitalist economy is negatively related to the share of consumption credit in total net credit, when the total credit is large to begin with.
Keywords: B51; O1; 330; circuit of capital; economic growth; consumption credit; Marxian political economy